2010
DOI: 10.1021/ma1017499
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Counteranion on the Thermal and Solution Behavior of Poly(2-(dimethylamino)ethyl methacrylate)-Based Polyelectrolytes

Abstract: Poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) was synthesized and subsequently neutralized with various acids to form PDMAEMA 3 HCl, PDMAEMA 3 HBF 4 , and PDMAEMA 3 HOTf polyelectrolytes. In addition, ion exchange of the chloride anion provided polyelectrolytes with NO 3 -, N(CN) 2 -, PF 6 -, and Tf 2 N -anions. The glass transition temperature (T g ) varied significantly with anion in the order Cl -> PF 6 -> BF 4 -> NO 3 -> TfO -> Tf 2 N -. The polyelectrolytes with larger, weakly coordinated anions req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
67
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 43 publications
10
67
0
Order By: Relevance
“…Long and co-workers also investigated the impact of counteranion on the solution and thermal properties of ammoniumbased polyelectrolytes. [ 11 ] Our study revealed the important infl uence of anion selection on the T g of the polyelectrolyte, and we observed polyelectrolyte electrospinning …”
supporting
confidence: 53%
See 1 more Smart Citation
“…Long and co-workers also investigated the impact of counteranion on the solution and thermal properties of ammoniumbased polyelectrolytes. [ 11 ] Our study revealed the important infl uence of anion selection on the T g of the polyelectrolyte, and we observed polyelectrolyte electrospinning …”
supporting
confidence: 53%
“…Our previous studies established the significant impact of counteranion selection on the thermal stability of cationic polyelectrolytes. [ 11 ] TGA of imidazolium-based PILs also displayed a similar trend with anion selection. Decreasing the basicity of the counteranion in the following order Br − > BF 4…”
Section: Methodsmentioning
confidence: 59%
“…This fact was related to the 193 zwitterionic nature of the lecithin which presents asymmetric positive and negative electric 194 charges. These charges were dissociated in aqueous solution and thus, led to an increase of 195 the electrical conductivity (Hunley, England & Long, 2010). Concerning the viscosity, it was 196 seen that very low values were obtained regardless the absence or presence of the 197 surfactants.…”
Section: Characterization Of the Carbohydrate-based Solutions 107mentioning
confidence: 99%
“…For example, the samples poly (BImBHCS-Br) and poly(BImBHCS-BF 4 ) with relative small volume have stable LC ordered structure when varying the temperature. The volume of PF 6 " is bigger than that of Br" and BF 4 " [57,58] and the poly(BImBHCS-PF 6 ) exhibited an isotropic transition temperature during the heating process. The counter-anion TFSI" had the largest volume and not only can it weaken the intramolecular stacking of biphenyl but it was shown to destroy the scaffold of main chain LC properties.…”
Section: Thermal Properties and Liquid Crystalmentioning
confidence: 94%
“…The observed T g trend resulted from the different nucleophilicity and steric effect of counter-anions [56]. For example, the TFSI" anion, which has relatively large steric hindrance and weak nucleophilicity, aided in the segmentmovement strengthening of the material [57,58], and thus this material (poly(BImBHCS-TFSI)) gave the lowest T g temperature among the four samples. To study the LC properties of the class of MCSCILCPs prepared herein, we performed PLM to investigate their birefringence phenomena.…”
Section: Thermal Properties and Liquid Crystalmentioning
confidence: 99%